Fuels and fuel-additives - Hancsók, Jenő, 1947- (John Wiley & Sons, Inc., 2013)
Covering the chemical structures and properties of fuels and fuel additives, Fuels and Fuels-Additives provides the science and technology involved in the production of energy efficient and environmentally friendly fuels and the role that fuel additives have in this process. This single source guide on fuels and fuel additives contains the most up-to-date coverage and requirements of the fuels including US and EU standards in automotive emissions, fuel quality and specifications, alternate fuels, biofuels, antioxidants, stabilizers and corrosion inhibitors, and polymeric fuel additives.